(untitled) (International Journal of Food and Nutritional Sciences, 2023)
Tuberculosis (TB) remains a global health challenge by the rise of drug-resistant Mycobacterium tuberculosis strains. Current treatments suffer from suboptimal efficacy and toxicity, necessitating new antitubercular agents. This study explores the potential of natural products from the mushroom Astraeus asiaticus. We conducted molecular docking studies of 64 metabolites against the MmpL3 protein, revealing several compounds with promising inhibitory potential. Metabolites with binding affinities between -6.5 to -8.7 using AutoDock Vina, were further analyzed using the SwissADME tool for drug-likeness and pharmacokinetic properties. Notably, compounds such as (E)-3-benzylidene-4-methyl-3, 4-dihydro-1H-benzo[e] [1,4] diazepine-2,5-dione (C17H14N2O2) and (13S) – 3 – hydroxy – 13 – methyl - 7, 8, 9, 11, 12, 13, 15, 16 – octahydro - 6H – cyclopenta [a] phenanthrene – 17 (14H) - one (C18H22O2) showed high binding affinity, stability, and favorable drug-likeness property. These findings suggest A. asiaticus as a promising natural source for new antituberculosis agents targeting MmpL3, providing a foundation for further in vitro and in vivo validation.